Multiple reformations?: the many faces and legacies of the Reformation - Stievermann, Jan; Zachman, Randall C. (Colloquia historica et theologica, 2018)
Dieser Band untersucht den inhärenten Pluralismus der Reformation und ihre mannigfaltigen Kulturwirkungen aus ökumenischem und interdisziplinärem Blickwinkel. Die Aufsätze beleuchten u.a. folgende Schlüsselfragen: Wie können wir heute die Reformation als ein historisches und theologisches Ereignis interpretieren und bewerten, wie als historiographische Kategorie und kulturellen Mythos? Und was sind die langfristigen globalen Konsequenzen der Reformationsepoche, wie sie sich in Gestalt miteinander konkurrierender konfessioneller Kulturen und letztlich unterschiedlicher globaler Christentümer manifestierten, im Kontext derer unterschiedliche Formen der Moderne entstanden?InhaltsübersichtJan Stievermann/Randall Zachman: Preface The Many Faces of the Reformation Euan Cameron: Reconsidering Early-Reformation and Catholic-Reform Impulses – Randall C. Zachman: The Birth of Protestantism? Or the Reemergence of the Catholic Church? How Its Participants Understood the Evangelical Reformation Interpretations of Scripture in the Reformation Period Manfred Oeming: The Importance of the Old Testament for the Reformer Martin Luther – Greta Grace Kroeker: Erasmus and Scripture – Paul Silas Peterson: »The Text of the Bible is Stronger«: The Rebirth of Scriptural Authority in the Reformation and it Significance The Reformation as an Interpretative Event Emidio Campi: The Myth of the Reformation – Scott Dixon: The German Reformation as a Historiographical Construct: The Shaping of the Narrative from Melanchthon to Walch – Ute Lotz-Heumann: Confessionalization is Dead, Long Live the Reformation? Reflections on Historiographical Paradigm Shifts on the Occasion of the 500th Anniversary of the Protestant Reformation The Aftermath of the Reformation Period John O'Malley: Catholic Pastoral Care: The Early Modern Period – Jan Stievermann: Early American Protestantism and the Confessionalization Paradigm: A Critical Inquiry Confessional Empires, Missions, and Nations Simon Ditchfield: The »Making« of Roman Catholicism as a »World Religion« – Patrick Griffin: The Last War of Religion or the First War for Empire? Reconsidering the Meaning of The Seven Years' War in America – Hartmut Lehmann: Nationalism as Poison in the Veins of Western Christianity, c. 1800 – c. 1950 Confessional Modernities, Enlightenment and Secularization John Betz: J. G. Hammann as a Radical Reformer: Two Mites Toward a Post-Secular, Ecumenical Theology – Volker Leppin: Friedrich Gogarten's Theology of Secularization Confessional Cultures: Legal and Diaconical Traditions Christoph Strohm: Confession and Law in Early Modern Europe – Johannes Eurich: The Influence of Religious Traditions on Social Welfare Development: Observations from the Perspective of Comparative Welfare State Research Scripture and the Evangelical-Pietist Tradition Ryan P. Hoselton: »Flesh and Blood Hath Not Revealed It«: Reformation Exegetical Legacies in Pietism and Early Evangelicalism – Douglas A. Sweeney: The Still-Enchanted World of Jonathan Edwards' Exegesis and the Paradox of Modern Evangelical Supernaturalism Scriptural Authority and Biblical Scholarship in the Nineteenth and Twentieth Centuries Friederike Nüssel: The Value of the Bible: Martin Kähler's Theology of Scripture and its Ecumenical Impact – David Lincicum: Ferdinand Christian Baur, the New Testament, and the Principle of Protestantism – Matthias Konradt: Sola Scriptura and Historical-Critical Exegesis